Epigenetic impairments in development of parthenogenetic preimplantation mouse embryos - Ngan Thi Kim HO; Thuy Van Thi NGUYEN; Thuan Van NGUYEN; Hong-Thuy BUI (The Society for Reproduction and Development, 2018)
Parthenogenesis is an activation process of oocytes that occur without the participation of sperm. Evidence suggests that normal development of embryos requires proper expression of several imprinted genes inherited from both the paternal and maternal genomes. Compared to gene expression, histone modifications and chromatin remodeling are not well-documented. In this research, by using immunofluorescence staining for several developmental-associated histone modifications, we investigated whether epigenetic impairments in parthenogenetic embryos act as constraints for proper development. At early stages, fertilized embryos exhibited high methylation of histone H3 at lysine 9 (Me-H3-K9) and Heterochromatin Protein 1 (HP1) present in the maternal chromatin, while paternal chromatin showed weaker HP1 signals. We found that at the two-cell stage in fertilized embryos, HP1, initially detected around the nucleolus, colocalized with chromocenters at one pole of the blastomere, while parthenotes showed a diffused distribution pattern of HP1 throughout the entire nucleoplasm. At the four-cell stage, methylation of histone H3 at arginine 26 (Me-H3-R26) increased at nascent RNA repression sites in fertilized embryos, while parthenotes recorded weaker signals throughout the nucleoplasm, suggesting differences in pluripotency of the ICM cells between the two types of embryos. Moreover, at the blastocyst stage, we observed that the acetylation level of histone H4 at lysine 12 (Ac-H4-K12) was significantly decreased in parthenogenetic ICM compared to that in its fertilized counterpart. To summarize, differences in epigenetic modifications correlating with paternal chromatin's capacity to regulate nascent RNA repression may contribute to aberrant development and lineage allocation in mouse parthenogenetic embryos.